The Use of Educational Technolgy During The Epidemic Spread For Arabic Skills/إستخدام تكنولوجيا التعليم أثناء انتشار الوباء لمهارات اللغة العربية - H M Riyadi (Jurnal Al-Maqoyis, 2021)
That learning technology has many benefits in its use during a pandemic in Arabic learning to improve Arabic language learning, both in its planning, implementation and evaluation. Therefore, for Arabic language teachers during a pandemic in utilizing learning technology, they must be varied in making the material, presenting it, and giving assignments to increase the Arabic language maharah. The purpose of this study is to find out the use of learning technology during a pandemic at MAN Banjarmasin in increasing the Arabic language teaching and the supporting and inhibiting factors in its use. The methodology in this study uses a descriptive qualitative approach with data collection used: Observation, Interview and Documentation. The results in this study indicate that: 1) The use of learning technology during the pandemic at MAN Banjarmasin in increasing the Arabic language maharah varied in its planning, implementation, and evaluation and was able to increase student values in learning Arabic. 2) factors that support and hinder the lack of provision of facilities and infrastructure, lack of IT mastery, enthusiasm and enthusiasm of teachers and students with online learning, professional language teachers, high student interest, provision of varied materials.